2005
DOI: 10.1002/andp.200410138
|View full text |Cite
|
Sign up to set email alerts
|

Darboux transformation for two-level system

Abstract: We develop the Darboux procedure for the case of the two-level system. In particular, it is demonstrated that one can construct the Darboux intertwining operator that does not violate the specific structure of the equations of the two-level system, transforming only one real potential into another real potential. We apply the obtained Darboux transformation to known exact solutions of the two-level system. Thus, we find three classes of new solutions for the two-level system and the corresponding new potential… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
2

Year Published

2005
2005
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 11 publications
1
31
0
2
Order By: Relevance
“…The first exact solution of the spin equation was found by Rabi [12] for an external field of the form F = (f 1 cos ωt, f 2 sin ωt, F 3 ), where f 1,2 , ω, and F 3 are real constants. A number of exact solutions of the spin equation were found in [8,13,14]. For periodic, or quasiperiodic, external fields, the equations of a two-level system have been studied by many authors using different approximation methods, e.g., perturbative expansions [15], see also [16].…”
Section: Spin Equationmentioning
confidence: 99%
See 1 more Smart Citation
“…The first exact solution of the spin equation was found by Rabi [12] for an external field of the form F = (f 1 cos ωt, f 2 sin ωt, F 3 ), where f 1,2 , ω, and F 3 are real constants. A number of exact solutions of the spin equation were found in [8,13,14]. For periodic, or quasiperiodic, external fields, the equations of a two-level system have been studied by many authors using different approximation methods, e.g., perturbative expansions [15], see also [16].…”
Section: Spin Equationmentioning
confidence: 99%
“…In [14], one can find several functions f (t) for which exact solutions of the spin equation can be found.…”
Section: Constant Spin Interactionmentioning
confidence: 99%
“…We note a decrease of the oscillation amplitude when δ approaches its critical value equal √ 3/2. This is why for δ close enough to the value √ 3/2 the minimal value of the probability P The result we have just obtained suggests us to consider a more general case [9,10], where function ǫ(τ ) being periodical depends on three parameters. One of them we fix by re-scaling both time and another parameter (frequency ω appearing in Eq.…”
Section: Dynamical Qubit Controllingmentioning
confidence: 79%
“…This leads to a solution obtained in [4]. We have found that equation (8) becomes very involved for the next transformation step.…”
Section: Transformations Of the Rabi Oscillationsmentioning
confidence: 87%
“…The function f 0 (t) plays the role of a "potential" in the non-Hermitian Dirac-like Hamiltonian h 0 (2). (For further details, see [3][4][5]. )…”
Section: Introductionmentioning
confidence: 98%